1988
DOI: 10.1152/ajpheart.1988.255.2.h397
|View full text |Cite
|
Sign up to set email alerts
|

Kinins induce abnormal vascular reactivity

Abstract: Previous studies have shown that after experimental neural trauma or acute hypertension the brain produces superoxide anion radicals, and brain arterioles display endothelial lesions, dilation, and loss of normal reactivity in response to a decrease in CO2 tension. Because these abnormalities are prevented by pretreatment with free radical scavengers or inhibitors of the cyclooxygenase component of prostaglandin (PG) H synthase, arachidonic acid metabolism by PGH synthase with concomitant formation of tissue i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In addition, autoradiographic studies have identified specific bradykinin binding sites in the brain and spinal cord (Fujiwara et al, 1989;Privitera et al, 1992). Kinin formation and activity has been demonstrated during different forms of CNS trauma, including brain lesion injury and cerebral ischaemia (Maier-Hauff et al, 1984;Unterberg et al, 1986;Ellis et al, 1987Ellis et al, , 1988Kamiya et al, 1990Kamiya et al, , 1993Wahl et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, autoradiographic studies have identified specific bradykinin binding sites in the brain and spinal cord (Fujiwara et al, 1989;Privitera et al, 1992). Kinin formation and activity has been demonstrated during different forms of CNS trauma, including brain lesion injury and cerebral ischaemia (Maier-Hauff et al, 1984;Unterberg et al, 1986;Ellis et al, 1987Ellis et al, , 1988Kamiya et al, 1990Kamiya et al, , 1993Wahl et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The components of the kinin‐kallikrein system are also expressed in brain (Walker et al, 1995). In the brain, elevated extracellular levels of bradykinin are found in cerebral trauma and ischemia (Ellis et al, 1988 ; Kamiya et al, 1993). As in peripheral tissue, bradykinin can increase the permeability of brain capillaries (Wahl et al., 1988).…”
mentioning
confidence: 99%
“…As in peripheral tissue, bradykinin can increase the permeability of brain capillaries (Wahl et al., 1988). This effect of bradykinin has been exploited to open the blood‐brain barrier for chemotherapy in brain tumors (Matsukado et al, 1996), but may also underlie the vasogenic brain edema found in cerebral ischemia (Kamiya et al, 1993 ; Relton et al, 1997) and trauma (Ellis et al, 1988).…”
mentioning
confidence: 99%
“…Recently, the kallikrein-kinin system has been implicated in posttraumatic vascular injury of the CNS (Ellis et al, 1987(Ellis et al, , 1988(Ellis et al, , 1989 and in vasogenic brain edema (Maier-Hauff et al, 1984;Unterberg and Baethmann, 1984;Unterberg et al, 1986). Recently, the kallikrein-kinin system has been implicated in posttraumatic vascular injury of the CNS (Ellis et al, 1987(Ellis et al, , 1988(Ellis et al, , 1989 and in vasogenic brain edema (Maier-Hauff et al, 1984;Unterberg and Baethmann, 1984;Unterberg et al, 1986).…”
mentioning
confidence: 99%
“…Vascular injury plays an important role in traumatic damage of the CNS. Recently, the kallikrein-kinin system has been implicated in posttraumatic vascular injury of the CNS (Ellis et al, 1987(Ellis et al, , 1988(Ellis et al, , 1989 and in vasogenic brain edema (Maier-Hauff et al, 1984;Unterberg and Baethmann, 1984; Unterberg et al, 1986). Vasoactive kinins, including bradykinin and Tkinin, among others, are released from their macromolecular kininogen precursors by proteolytic enzymes, the tissue or T-kininogenase kallikreins (Muller-Ester1 et al, 1986).…”
mentioning
confidence: 99%